Probiotics and synbiotics for the prevention of postoperative infections following abdominal surgery: a systematic review and meta-analysis of randomized controlled trials. Issue 2 (February 2016) - Lytvyn, L.; Quach, K.; Banfield, L.; Johnston, B.C.; Mertz, D.
Summary: Background: Postoperative infections, particularly surgical site infections (SSIs), cause significant morbidity and mortality. Probiotics or synbiotics are a potential prevention strategy. Aim: To evaluate the efficacy of probiotics/synbiotics for reducing postoperative infection risk following abdominal surgery. Methods: We searched AMED, Central, CINAHL, Embase, Medline, and grey literature for randomized controlled trials of elective abdominal surgery patients administered probiotics or synbiotics compared to placebo or standard care. Primary outcome was SSIs. Secondary outcomes were adverse events, respiratory tract infections (RTIs), urinary tract infections (UTIs), combined infections, length of hospital stay, and mortality. Using random-effects meta-analyses, we estimated the relative risk (RR) or mean difference (MD) and 95% confidence interval (CI). Tests were performed for heterogeneity, subgroup and sensitivity analyses were conducted, and the overall evidence quality was graded. Findings: We identified 20 trials ( N  = 1374 participants) reporting postoperative infections. Probiotics/synbiotics reduced SSIs (RR: 0.63; 95% CI: 0.41–0.98; N  = 15 studies), UTIs (RR: 0.29; 95% CI: 0.15–0.57; N  = 11), and combined infections (RR: 0.49; 95% CI: 0.35–0.70; N  = 18). There was no difference between groups for adverse events (RR: 0.89; 95% CI: 0.61–1.30; N  = 6), RTIs (RR: 0.60; 95% CI: 0.36–1.00; N  = 14), length of stay (MD: −1.19; 95% CI: −2.94 to 0.56; N  = 12), or mortality (RR: 1.20; 95% CI: 0.58–2.48; N  = 15). Conclusion: Our review suggests that probiotics/synbiotics reduce SSIs and UTIs from abdominal surgeries compared to placebo or standard of care, without evidence of safety risk. Overall study quality was low, owing mostly to imprecision (few patients and events, or wide CIs); thus larger multi-centered trials are needed to further assess the certainty in this estimate.